Time Series Forecasting of Nickel Sales in Nickel Mining Companies Listed on Indonesia Stock Exchange (IDX) - Farah Ayu Mufida; Nurafni Eltivia; Nur Indah Riwajanti (eCo-Fin, 2024)
This research aims to analyze nickel sales forecasting using time series forecasting with the help of Microsoft Excel and then compare the pattern between Nickel Mining Companies listed on IDX (Indonesia Stock Exchange). This research uses a quantitative descriptive study with a forecasting method. The data used is secondary data, which is sales data contained in the financial statements of nickel mining companies listed on the IDX (Indonesia Stock Exchange) from 2015-2023. There are a total of 43 data. The results of this study show that the highest sales forecast from PT Aneka Tambang Tbk's nickel sales is in quarter 4 of 2024 of IDR 16,4 trillion, and the lowest forecast is in quarter 1 of 2024 of IDR 3,4 trillion. On the other hand, the highest nickel sales forecast from PT Vale Indonesia Tbk is in the 4th quarter of 2024 of IDR 19,3 trillion, and the lowest forecast is in the 1st quarter of 2024 of IDR 4,3 trillion. The patterns formed on the forecasting plot graphs of the two companies tend to be the same. The sales trend and forecasting trend are also the same, there is an increase and show good business prospects and nickel sales.